Pembinaan Olahraga Renang di SD Muhammadiyah 1 di Kota Malang - Irellia Greavil Wahyono; Supriatna Supriatna (Publikasi Indonesia, 2023)
Swimming is an individual or team racing sport that requires the use of one's entire body to move through water. This sport takes place in swimming pools or open water (for example, in the ocean or lake). The purpose of this research is to recognize coaching, training programs, organizations, and infrastructure facilities as the main aspects of the implementation of swimming sports coaching at SD Muhammadiyah 1 in Malang City. The approach taken in this study is information in the form of observation, documentation and interviews. In the swimming coaching research of SD Muhammadiyah 1, it can be concluded that the coaching carried out to students is good and communicative. Management organizations are listed in good and organized criteria. The facilities and infrastructure owned are adequate and have relatively good requirements.